Inclusive Education based on the 9-Layered Model of Giftedness and the Role of Digital Technologies - Karyotaki, Maria; Lele, Chrysoula; Charalabos Skianis (Eximia, 2022)
We present a pioneering framework in the field of education based on inclusive teaching and learning practices and techniques in the classroom. Adaptable and immersive learning experiences centered on the enhancement of cognitive skills throughout the school curriculum can provide a positive whole school ethos. The current framework as a product of transdisciplinary research in ICTs, Cognitive Science and Education sets the example for the implementation of blended learning environments, combining both physical and virtual learning experiences to set the ground for inclusive and flexible educational curriculum.